Microvasculature recovery in lamina cribrosa and peripapillary sclera after glaucoma surgery and its impact on visual field progression - Hee Jong Shin; Hee Kyung Ryu; Seong Ah Kim; Younhea Jung; Chan Kee Park; Hae-Young Lopilly Park (Scientific Reports)
Abstract This study investigates vessel density (VD) changes in the lamina cribrosa (LC) and peripapillary sclera (PPS) after glaucoma surgery and their association with visual field (VF) progression. Primary open-angle glaucoma patients undergoing surgery for uncontrolled intraocular pressure (IOP) at Seoul St. Mary’s Hospital were included. Optical coherence tomography angiography (OCT-A) assessed VD changes in the LC and PPS one month post-surgery. VF progression was evaluated using mean deviation (MD) values from serial VF tests over six months. Of 80 enrolled eyes, 74 were analyzed. Laminar VD recovery occurred in 12 eyes (16.2%), with a 21.92% ± 7.37% increase, linked to shorter axial length (P = 0.005), thinner corneal thickness (P = 0.016), and less PPS VD change (P < 0.001). PPS VD recovery occurred in 14 eyes (18.9%), with an 18.50% ± 7.28% increase, associated with younger age (P = 0.043), longer axial length (P = 0.010), and lower preoperative PPS VD (P < 0.001). Multivariate analysis showed that both laminar and PPS VD recovery significantly reduced VF progression risk (P < 0.001). VD recovery, particularly in the LC, predicts better glaucoma outcomes. The distinct responses of LC and PPS to IOP reduction highlight the need to consider individual anatomical factors in glaucoma management.